Conservation and restoration of montane forest communities in Thailand - Werner, Wolfgang L.; Thawatchai Santisuk (Restoration of tropical forest ecosystems, 1993)
Montane rain forests form the natural vegetation of Thailand, usually at the elevation above 900-1000 m a.s.l. But these evergreen montane rain forests are heavily subjected to various types of land-use. A frequent and somewhat reversible form of degradation is the lower montane oak forest with an impoverished flora and a dominance of Fagaceae, Lauraceae, Magnoliaceae and Theaceae, as well as other pioneer species following shifting cultivation. Frequent surface fires and poor sandy soil render the invasion of Pinus kesiya to form lower montane pine-oak forest. Deciduous dipterocarp forest and pine-deciduous dipterocarp forest with Pinus merkusii occurring sometimes up to 1350 m a.s.l. are also maintained by annual surface fire and thereby creating a more or less open forest in nature.